MERESPONS TANTANGAN ABAD KE-21: Redefinisi Kurikulum PAI Melalui Pendekatan Kompetensi - Siagian, Hairun Nisa; Silaen, Irma Sulistia; Hsb, Fahmi Nurjannah; Halimah, Siti (UIN Sumatera Utara, 2025)
Abstract: The Islamic Religious Education curriculum has an important role in shaping the character and spiritual abilities of students in accordance with the demands of the competency-based curriculum. Objectives, content/materials, learning strategies, and evaluation are the main components of the Islamic Education curriculum. This study used a qualitative approach, using descriptive-analytical methods and document studies, to analyse the relationship and role of each component to ensure that educational goals are optimally achieved. The results showed that the four elements encourage each other and must be planned in an integrated manner so that PAI learning can run effectively, contextually, and in accordance with the times. The results of this study are expected to be the basis for developing a customised PAI curriculum that is able to form a competent and characterful Muslim generation.Keywords: Islamic Education Curriculum, Curriculum Components, Islamic Religious Education